Solar reflective ink-jet printed porcelain stoneware tiles as an alternative for Urban Heat Island mitigation. Issue 2 (February 2022) - Cedillo-González, E.I.; Governatori, M.; Ferrari, C.; Siligardi, C.
Highlights: Ink-jet printed porcelain stoneware tiles for UHI mitigation were prepared. A zircon containing engobe with a good ability to reflect solar radiation was used. Two printing modes, five printing intensities, and four colours were tested. Some of the prepared tiles fall in the general definition of cool colors ( ρ sol ≥ 0.50). The solar reflectance depends on engobe's coverage (by inks) and inks' composition. Abstract: Digital ink-jet printing is a decoration system for ceramic tiles that requires the application of engobes with high whiteness and opacity, characteristics that can be used to design solar reflective ink-jet decorated tiles. These materials can help to mitigate Urban Heat Island (UHI) phenomenon. Here, the fabrication of ink-jet printed solar reflective tiles using an engobe with high solar reflectance was investigated. Two printing modalities (binary (BIN) and grayscale (GS)), five printing intensities, and four colours were tested. It was found that some of the prepared tiles can be used for mitigating the UHI phenomenon. The solar reflective properties were mainly derived from the reflective engobe, and in some grade, from the mineral composition of the inks. The colour and roughness measurements revealed that the GS modality could prepare ink-jet decorated tiles with good solar reflective properties with a smaller quantity of inks and good soiling resistance.